Science of running : analyze your technique, prevent injury, revolutionize your training - Napier, Chris; Lewis, Arran (New York ; London : Dorling Kindersley, 2020)
"Science of Running answers all your running-related questions, from what's going on in your lungs during a sprint to the science behind the legendary "runner's high." Learn how to run faster, further, and for longer--scientifically." -- provided by publisher
Running anatomy -- Preventing injury -- Strength exercises -- How to train.
Includes bibliographical references (pages 222-223) and index.
Keywords: Running -- Physiological aspects; Running -- Training; Sports medicine; Marathon running; Running races; Running injuries -- Prevention; HEALTH & FITNESS / Exercise; SPORTS & RECREATION / Running & Jogging; SPORTS & RECREATION / Training; Sports medicine; Running -- Training; Running races; Running injuries -- Prevention; Marathon running; Running -- Physiological aspects; Handbooks and manuals; Handbooks and manuals